The Ability of Eleventh Grade Students at SMA Negeri 3 Ambon in Write Poetry Using Natural Media - Everhard Markiano Solissa; Jolanda Dessye Parinussa (East Asian Journal of Multidisciplinary Research, 2022)
Writing is one of four language skills. Of the four language skills, writing ranks last. That is, the ability to write can be achieved if the other three skills (listening, speaking, and reading) have been acquired first. The ability to write poetry is one of the competencies that must be mastered by junior high school students. The fact proves that not all junior high school students are able to write well, especially writing poetry. Therefore, it is necessary to conduct research to identify and overcome these problems. The purpose of this study was to describe the ability to write poetry through natural media of class XI students of SMA Negeri 3 Ambon. The method used is descriptive quantitative method using statistical formulas and calculations. The main data of this study were collected by test technique. The test was conducted on 30 students. The results showed that the ability of eleventh grade students at SMA Negeri 3 Ambon in write poetry using natural media was good.